2009
DOI: 10.1080/19312430802631467
|View full text |Cite
|
Sign up to set email alerts
|

Selling News: Behind the Content of Cable and Broadcast Morning Shows

Abstract: Through content analysis of the three broadcast networks and two leading cable news channels, this study's authors (1) examine how promotional content fits into the overall lineup of the morning news shows, (2) evaluate ownership patterns as they relate to this content, and (3) examine the policy implications of news decisions related to promotional content. The study identifies clear differences in the practices of the broadcast versus cable morning news programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(16 reference statements)
2
5
0
2
Order By: Relevance
“…El estudio de mensajes autorreferenciales en los espacios editoriales audiovisuales tiene una larga trayectoria (Cleary & Coffey, 2009;Coffey & Cleary, 2011;Jung, 2001;McAllister, 2002;Price, 2003;Williams, 2002), pero esa línea de trabajo no está especialmente desarrollada en España, si consideramos las escasas investigaciones al respecto (De Lara, Rodríguez & Sánchez, 2011). Tal vacío probablemente responde al hecho de que el uso de las sinergias en las estrategias promocionales en el sector de la comunicación es relativamente reciente en el continente europeo (Hendrickson & Wilkins, 2009, p. 379).…”
Section: La Autorreferencia En Los Informativos: Los Mensajes Autoprounclassified
“…El estudio de mensajes autorreferenciales en los espacios editoriales audiovisuales tiene una larga trayectoria (Cleary & Coffey, 2009;Coffey & Cleary, 2011;Jung, 2001;McAllister, 2002;Price, 2003;Williams, 2002), pero esa línea de trabajo no está especialmente desarrollada en España, si consideramos las escasas investigaciones al respecto (De Lara, Rodríguez & Sánchez, 2011). Tal vacío probablemente responde al hecho de que el uso de las sinergias en las estrategias promocionales en el sector de la comunicación es relativamente reciente en el continente europeo (Hendrickson & Wilkins, 2009, p. 379).…”
Section: La Autorreferencia En Los Informativos: Los Mensajes Autoprounclassified
“…; and, if it is occurring, what are the potential negative consequences? Although some monitoring of the traditional news space has been conducted (Cleary & Adams-Bloom, 2009a, 2009bHendrickson & Wilkins, 2009;Jung, 2001;Williams, 2002;Wood, Nelson, Cho, & Yaros, 2005), few studies have analyzed the content of newly emerging media spaces to try to understand how news programmers may, or may not, be using this new media space as real estate for promotion, branding, or synergistic content related to their own firms. Moreover, how does the strategic use of new media spaces compare to that of traditional media spaces?…”
Section: In An Integrated Media Environment Where News Network Seek mentioning
confidence: 99%
“…Evidence is mixed as to whether news programmers compromise editorial integrity for promotional gain. Studies of morning news shows and their promotion of parent-company produced entertainment products (Adams-Bloom & Cleary, 2009;Cleary & Adams-Bloom, 2009a, 2009bHendrickson & Wilkins, 2009) have indicated that there is a tendency for news organizations to favorably feature parent company products in their entertainment news coverage, often without revealing the corporate connection. Others have also cited a tendency for news programmers to mix obligations to viewers and corporate owners.…”
Section: Promotion and Branding Theorymentioning
confidence: 99%
“…The proliferation of media cross-ownership, which refers to ‘the ownership of multiple media businesses by a person or corporation’ (Park, 2014: 44), is driven by at least two different forces. In efforts to offset the weakening of financial stability and survive, news media businesses are acquiring other media companies as subsidiaries to increase their revenue or to produce synergetic effects that financially benefit both the parent companies and their subsidiaries (Cleary and Adams-Bloom, 2009a, 2009b; Hardy, 2010; Santin and Rubira, 2014). Meanwhile, emerging technologies, such as the Internet-based news, are blurring the boundaries between the traditional newsroom and the convergence of various channels of new media (Noam, 2017; Terry, 2013; Wagner and Collins, 2014).…”
mentioning
confidence: 99%
“…Based on these trends, scholars are expressing concerns about whether and how the structure of media cross-ownership influences news content as well as journalism practices (Cleary and Adams-Bloom, 2009a, 2009b; Hardy, 2010; Panis et al, 2015). Specifically, those concerns focus on the extent to which media cross-ownership is likely to increase self-coverage and cross-promotion (Panis et al, 2015; Santin and Rubira, 2014).…”
mentioning
confidence: 99%